Pengaruh Brand Image, Harga dan Kualitas Produk Terhadap Loyalitas Pelanggan McDonald's Jakarta Timur - Sari, Dian Indah (Jurnal EMT KITA, 2023)
The purpose of this research is to determine the influence of brand image, price, and product quality on customer loyalty at McDonald's East Jakarta. This type of associative research is used in this study. The data collection technique uses a questionnaire of 100 East Jakarta McDonald's customer respondents. The sampling technique in this study used Non-Probability Sampling, namely simple random sampling. The data analysis technique used in testing the research hypothesis is the use of the SPSS program. The above problems resulted in the following conclusions: 1. Brand Image has a positive and significant effect on customer loyalty. 2. Price has a positive and significant effect on customer loyalty. 3. Product quality has a positive and significant influence on customer loyalty. 4. Brand image, price and product quality have a positive and significant influence on customer loyalty at McDonald's East Jakarta.